A checklist of the New World chafers (Coleoptera: Scarabaeidae: Melolonthinae) - Evans, Arthur V. (Zootaxa, 2003)
A checklist and bibliography of the New World Melolonthinae are presented. As of 31 December 2002, the New World melolonthine fauna consists of 11 tribes, 122 genera, and 2,705 valid species, including 11 fossil species. The checklist is a synthesis of the tribal classifications of Blackwelder (1944), Britton (1978) and Evans (2002). Seven new combinations, eleven replacement names, and eight new synonymsare recognized. Thirteen varietal names were evalutated and determined to be subspecific in rank. The type species of 21 genera are here designated. Three genera and one species are listed as incertae sedis. Since the catalogs of Dalla Torre (1912, 1913) and Blackwelder (1944) two genera and two species have been removed from the New World Melolonthinae. Sericoides nossi Martínez, 1971 and Sericoides rechencqui Martínez, 1971 are nomina nuda.